Modern Transport Telematics 11th International Conference on Transport Systems Telematics, TST 2011, Katowice-Ustroń, Poland, October 19-22, 2011. Selected Papers - Mikulski, Jerzy (Communications in Computer and Information Science, 2011)
This book constitutes the proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems, SSS 2011, held in Grenoble, France, in October 2011. The 29 papers presented were carefully reviewed and selected from 79 submissions. They cover the following areas: ad-hoc, sensor, and peer-to-peer networks; safety and verification; security; self-organizing and autonomic systems; and self-stabilization.